JARINGAN AKTOR POLITIK LOKAL DALAM RELASI TRADISI BELIS (STUDI KASUS MASYARAKAT KABUPATEN ROTE NDAO) - Zacharias, Andrew Ermico; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2018)
ABSTRACT The Political history of the government was intervend of Political Actors in custom tradition is a problem inherent in the district of Rote Ndao, NTT Province. The research is to find out the role of Political Actors in playing the traditional ritual of Belis in DPRD and government political legitimacy and knowing the existence of interest and the power relations in Belis are useful for building a network in the Rote Ndao district of NTT Province. The theory used is Patron Klient theory, Identity Politics, and Power Networks. This research method is qualitative descriptive. Result collection techniques with in-depth interviews, observations, and documents. The results of this Belis tradition relationship in Rote could not be separated with that ethnic and religious identity factors.This study also received intervention from political actors in the Belis tradition who were interested in building a useful power relationship in Rote Ndao district. Keywords : Political Actors, Belis, Ethnic Religion, Indigenous Groups, and Power Networks